Shear wave elastography of the maternal cervix: A transabdominal technique - O'Hara, S.; Zelesco, M.; Sun, Zhonghua (2018)
Introduction: Reduced cervical length as seen on transvaginal ultrasound is a strong indicator of spontaneous preterm birth in the high-risk population. In low-risk women the appropriate method to assess this risk is still debatable. Ultrasound elastography has been used to assess cervical strength. This research aimed to assess the accuracy of shear wave speeds (SWS) obtained deep to echo free fluid-filled structures, and the use of two-dimensional shear wave on the maternal cervix using a transabdominal ultrasound approach. Method: Agreement of SWS measurements obtained through fluid and directly onto an ultrasound phantom was assessed for accuracy. Speed measurements were obtained in the anterior and posterior portions of the internal and external cervical os on 50 gravid participants in the mid-trimester of pregnancy. Results: No difference in SWS was obtained in the phantom with either direct contact or through the saline water-bath (P > 0.05). In 50 participants, measurements were obtainable at the external os anterior and posterior in 49 and 38 participants, respectively, and in 47 and 42 participants for internal os anterior and posterior. The mean speed obtained at the external os anterior and posterior was 2.01 0.51 and 2.38 0.47 m/s, respectively, and at the internal os anterior and posterior, 2.49 0.50 and 2.58 0.41 m/s. Conclusion: Shear wave speed measurements can be obtained in the maternal cervix using a transabdominal approach with a moderately full maternal bladder in most patients, with a larger number of shear wave measurements obtained in the anterior cervix compared to posterior.